2003
DOI: 10.1098/rstb.2003.1289
|View full text |Cite
|
Sign up to set email alerts
|

Plant introductions, hybridization and gene flow

Abstract: Many regional floras contain a high proportion of recently introduced plant species. Occasionally, hybridization between an introduced species and another species (introduced or native) can result in interspecific gene flow. This may occur even in instances where the F 1 hybrid shows very high sterility, but occasionally produces a few viable gametes. We provide examples of gene flow occurring between some rhododendrons recently introduced to the British flora, and between an introduced and native Senecio spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
124
0
1

Year Published

2004
2004
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(126 citation statements)
references
References 68 publications
1
124
0
1
Order By: Relevance
“…However, we reiterate the point we made in section 2.1.2, that biologists face the same problem, for example, with horizontal gene transfer in bacteria (Doolittle 1999;Rivera & Lake 2004) and plants (Abbott et al 2003). Although we agree with Borgerhoff Mulder et al that it is vital that the parallels between biological and cultural evolution should not blind researchers to the differences, the significance of horizontal transfer to the two disciplines is a matter of degree, not kind.…”
Section: R38 Assumptions Underlying Cultural Phylogeniessupporting
confidence: 59%
See 1 more Smart Citation
“…However, we reiterate the point we made in section 2.1.2, that biologists face the same problem, for example, with horizontal gene transfer in bacteria (Doolittle 1999;Rivera & Lake 2004) and plants (Abbott et al 2003). Although we agree with Borgerhoff Mulder et al that it is vital that the parallels between biological and cultural evolution should not blind researchers to the differences, the significance of horizontal transfer to the two disciplines is a matter of degree, not kind.…”
Section: R38 Assumptions Underlying Cultural Phylogeniessupporting
confidence: 59%
“…However, as noted by , any putative dichotomy contrasting a "divergent, branching biological evolution" with a "convergent, cross-fertilising cultural evolution" is a distortion of both biology and culture. Significant cross-lineage transfer occurs in biological evolution, especially for microbes (Doolittle 1999;Rivera & Lake 2004) and plants (Abbott et al 2003), whereas the convergent nature of culture is an empirically testable hypothesis rather than a statement of fact. Tackling the issue systematically and quantitatively, Tehrani and Collard (2002) found a greater role for branching "phylogenesis" than convergent "ethnogenesis" in Turkmen textile patterns, and Collard et al (2005) have found that the best available cultural data sets show just as good a fit with a branching phylogenetic model as do biological data sets.…”
Section: Macroevolutionmentioning
confidence: 99%
“…Previous reports have shown that although hybrid fertility is greatly reduced backcross progeny can be obtained, with fertility increasing in subsequent generations (Tranel et al, 2002). Moreover, for hybrids to be evolutionary meaningful, they need to show a comparative advantage with respect to the original population (Abbott et al, 2003). The acquisition of herbicide resistance via single gene movement, combinatorial gene action, or other hybrid-related mechanism could provide hybrids with such comparative advantage.…”
Section: Field Hybridization Between Amaranthus Spmentioning
confidence: 99%
“…Like biological transmission, culture is transmitted from parents to offspring, and like cultural transmission, which is transmitted horizontally to unrelated individuals, so in microbes and many plant species, genes are regularly transferred across lineage boundaries [6,24,25]. Moreover, anthropologists reconstruct the history of social groups by analysing homologous and analogous cultural traits, much as biologists reconstruct the evolution of species by the analysis of shared characters and homologous DNA [26].…”
Section: Gene -Culture Coevolutionmentioning
confidence: 99%